(untitled) (Research, Society and Development, 2021)
Intending to highlight new fruits with nutraceutical potential, the present work reports the nutritional and antioxidant content of Syzygium cumini (L.) Skeels (S. cumini) and Syzygium malaccense (L.) Merr. & LM Perry (S. malaccense), and evaluates the anticancer potential against CP-H460 (lung carcinoma line) and its functionality over HEK-293 (healthy embryonic kidney line), two human cells. For this, the physical-chemical characterization of the lyophilized fruits was carried out, and the content of total phenolic compounds (Folin-Ciocalteau) and the antioxidant potential (DPPH, FRAP, and ORAC) was determined. For anticancer activity, aqueous extracts were prepared and evaluated using the MTT (3-[4,5-dimethyl-triazol-2-yl]-2,5-diphenyltetrazolium) assay for periods of 20 hours. These two species are rich in dietary fibers, mainly insoluble fibers, and are sources of natural compounds and antioxidants, which possibly explain the protective potential against cancer cells. Thus, it is expected, as two source fruits, results obtained (p <0.01), mainly S. cumini in contact with CP-H460, which reduces the growth of a cell with lung carcinoma. This finding revealed that these fruits have antiproliferative activity against a lung carcinoma cell, where the highest concentration tested (2 mg/mL) was able to inhibit almost 80% of cell proliferation. Besides, when S. cumini was evaluated in HEK-293, all concentrations evaluated showed cell viability superior to the positive control (p <0.01). In conclusion, both S. cumini and S. malaccense can be used as nutraceuticals in complementary therapies given their nutritional properties.